Estimating the benefits of R&D subsidies for Germany - Mila Koehler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
In Germany, R&D subsidies are an important tool to support innovation in the private sector. This paper studies the welfare effects of R&D subsidies distributed through the German federal government's thematic R&D programs between 1994 and 2011. The analysis is based on a structural model of the R&D subsidy process which allows to estimate the benefits of R&D subsides to the German economy. The model takes into account heterogeneous application costs of firms and identifies the effect of the subsidy on the federal government's utility as well as on firm profits. Assuming a welfare-maximizing federal government, the estimated average social rate of return is 34% for Germany in the period 1994 to 2011. Thereby effects on firm profits are similar to effects on spillovers to the rest of the German economy. Besides results show that the subsidy rate decision in Germany remained remarkably stable over time, and that application costs as well as the marginal profitability of subsidized R&D projects are lower after the year 2000 compared to the years before.
urn:nbn:de:bsz:180-madoc-441799
Keywords: D61; H25; L59; O31; O38; 330; R&D; Innovation; R&D Subsidies; Innovation Policy; Welfare Economics